Advances and Limitations on the Current Treatment for Schizophrenia and its Future Prospect - Li, Jianning; Zhang, Yunyang; Zhou , Ruoyu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Schizophrenia is a challenging mental disorder marked by recurring psychosis. This article provides an in-depth overview of the current status of research and treatment techniques for schizophrenia. The introductory part gives a thorough explanation of the illness, including all of its many phases and symptoms. The review analyzes the genes involved in cell signaling and neurotransmission, including NRG1, DTNBP1, DISC1, and RGS4, which are important contributors to schizophrenia susceptibility. The article discusses the limitations and challenges associated with existing treatment modalities, including antipsychotic drugs (both typical and atypical), transcranial magnetic stimulation, deep brain stimulation, virtual reality, electroconvulsive therapy, and the ketogenic diet. These approaches have demonstrated efficacy in managing different aspects of schizophrenia symptoms, but they also come with limitations such as side effects, individual variability in response, and ethical concerns. To overcome these limitations, the study offers CRISPR gene editing as a viable future therapeutic option. To improve the efficacy and safety of schizophrenia therapies, the conclusion underlines the need for tailored treatment planning, continuous research, and creative approaches. The changing landscape of schizophrenia research and therapy gives promise for better results and quality of life for people living with the condition.